2018
DOI: 10.1080/13548506.2018.1446098
|View full text |Cite
|
Sign up to set email alerts
|

Emotional responses to behavioral economic incentives for health behavior change

Abstract: Many people aim to change their lifestyle, but have trouble acting on their intentions. Behavioral economic incentives and related emotions can support commitment to personal health goals, but the related emotions remain unexplored. In a regret lottery, winners who do not attain their health goals do not get their prize but receive feedback on what their forgone earnings would have been. This counterfactual feedback should provoke anticipated regret and increase commitment to health goals. We explored which em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This comparison can turn out either good or bad, but there is always the risk of finding out you have won, but that your own behavior has resulted in having to give up the prize. The financial outcome may be identical as in a traditional lottery (smoking means no prize), but the anticipated emotion and intensity are expected to differ [ 48 ]. In national lotteries, the promise of this counterfactual feedback has motivated people to prevent regret and play, more often than in traditional lotteries where if you not decide to play, you never find out what would have happened if you had played [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This comparison can turn out either good or bad, but there is always the risk of finding out you have won, but that your own behavior has resulted in having to give up the prize. The financial outcome may be identical as in a traditional lottery (smoking means no prize), but the anticipated emotion and intensity are expected to differ [ 48 ]. In national lotteries, the promise of this counterfactual feedback has motivated people to prevent regret and play, more often than in traditional lotteries where if you not decide to play, you never find out what would have happened if you had played [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This way, participants know that they can compare the outcome of their decision to the counterfactual outcome, had they decided differently. If the alternative decision-option turned out better than the chosen option, people can feel regret [ 48 ]. More importantly, if people know in advance that they can compare outcomes, research shows that we anticipate regret and make regret-avoiding decisions [ 33 ].…”
Section: Interventionmentioning
confidence: 99%
“…Previous studies have demonstrated the importance of physical activity in decreasing chronic pain and improving functional outcomes [ 18 – 22 ], and behavioral incentives have successfully motivated non-veteran and non-chronic pain patients to engage in increased activity [ 27 32 , 41 ]. This study represents one of the first to test the use of a regret lottery to motivate veterans with chronic pain to increase their physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Both arms were encouraged to meet a weekly activity goal of either (a) a 5% increase in steps over the previous week, or (b) achieving and maintaining the number of steps at 150% over baseline; no specific exercise program was prescribed. Mirroring prior studies [ 28 , 40 , 41 ], the regret lottery provided participants in the intervention arm who met either activity goal the weekly chance of winning a small ($30; 18% chance of winning) or large ($100; 1% chance of winning) incentive. Participants in the intervention arm who did not meet their goal were informed what they would have won had they met their goal.…”
Section: Methodsmentioning
confidence: 99%
“…The same study also finds that medium intensity fear is more beneficial than maximal intensity. Van der Swaluw et al, (2018) nuance this a little by applying it to the negative emotions experienced when an individual fails to meet their goals. These rely on a straightforward response/stimulus nexus, whereby it is expected that the threat or expectation of something bad will prevent a particular form of action.…”
Section: Affect Politics and Behaviour Changementioning
confidence: 99%